Indirect Evidence for Genetic Differentiation in Vulnerability to Embolism in Pinus halepensis - David-Schwartz, Rakefet; Paudel, Indira; Mizrachi, Maayan; Delzon, Sylvain; Cochard, Hervé; Lukyanov, Victor; Badel, Eric; Capdeville, Gaelle; Shklar, Galina; Cohen, Shabtai (Frontiers in Plant Science, 2016)
Climate change is increasing mean temperatures and in the eastern Mediterranean is expected to decrease annual precipitation. The resulting increase in aridity may be too rapid for adaptation of tree species unless their gene pool already possesses variation in drought resistance. Vulnerability to embolism, estimated by the pressure inducing 50% loss of xylem hydraulic conductivity (P50), is strongly associated with drought stress resistance in trees. Yet, previous studies on various tree species reported low intraspecific genetic variation for this trait, and therefore limited adaptive capacities to increasing aridity. Here we quantified differences in hydraulic efficiency (xylem hydraulic conductance) and safety (resistance to embolism) in four contrasting provenances of Pinus halepensis (Aleppo pine) in a provenance trial, which is indirect evidence for genetic differences. Results obtained with three techniques (bench dehydration, centrifugation and X-ray micro-CT) evidenced significant differentiation with similar ranking between provenances. Inter-provenance variation in P50 correlated with pit anatomical properties (torus overlap and pit aperture size). These results suggest that adaptation of P. halepensis to xeric habitats has been accompanied by modifications of bordered pit function driven by variation in pit aperture. This study thus provides evidence that appropriate exploitation of provenance differences will allow continued forestry with P. halepensis in future climates of the Eastern Mediterranean.